2008
DOI: 10.1016/j.plantsci.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

In silico development of simple sequence repeat markers within the aeschynomenoid/dalbergoid and genistoid clades of the Leguminosae family and their transferability to Arachis hypogaea, groundnut

Abstract: Cultivated groundnut (Arachis hypogaea L.) is an agronomically and economically important oilseed crop grown extensively throughout the semi-arid tropics of Asia, Africa and Latin America. The genetic base of the cultivated groundnut is very narrow as a result of the genetic bottleneck associated with recent polyploidization which makes it critical to determine the levels of genetic diversity within available germplasm collections prior to breeding. In groundnut, the use of SSRs for diversity assessment may of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
23
0
4
Order By: Relevance
“…Those most recently reported include: 14 by Gimenes et al [27]; 51 by Mace et al [28]; 188 by Proite et al [29]; 104 by Cuc et al [30]; 138 by Yuan et al [31]; 33 by Song et al [32]; 123 by Wang et al [33]; 290 by Liang et al [34]; and 1,571 by Koilkonda et al [35]. Five hundred and ninety-eight of these markers are included in the A. duranensis map (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Those most recently reported include: 14 by Gimenes et al [27]; 51 by Mace et al [28]; 188 by Proite et al [29]; 104 by Cuc et al [30]; 138 by Yuan et al [31]; 33 by Song et al [32]; 123 by Wang et al [33]; 290 by Liang et al [34]; and 1,571 by Koilkonda et al [35]. Five hundred and ninety-eight of these markers are included in the A. duranensis map (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent SSR marker‐based genetic diversity studies revealed relatively moderate level of polymorphism in cultivated groundnuts (Gimenes et al. 2007, Mace et al. 2006, 2007, Kottapalli et al.…”
Section: Discussionmentioning
confidence: 99%
“…SSR markers have been found most successful in identifying molecular variation within the cultivated peanut species (Hopkins et al 1999;Ferguson et al, 2004aFerguson et al, , 2004bMace et al, 2006Mace et al, , 2007Cuc et al, 2008;Varshney et al, 2009;Khedikar et al, 2010;Mondal and Badigannavar, 2010;Gautami et al, 2011;Shirasawa, 2012;Sujay et al, 2012). However, a few RAPD markers have been successfully used in the identification of candidate genes of interest in peanut (Burow et al, 1996;Garcia et al, 1996;Mondal et al, 2007).…”
Section: Resultsmentioning
confidence: 99%